THEME: CLASSROOM MANAGEMENT IN AN INTENSIVE ENVIRONMENT - Safarova Dildora,; Jabborov Shaxzod,; Soibov Asl, (Ustozlar uchun, 2025)
This article explores effective strategies for managing classrooms in an intensive learning environment. It emphasizes the importance of setting clear expectations, maintaining discipline, fostering student engagement, and being flexible in teaching approaches. The discussion also highlights the significance of time management, communication, stress management, technology use, and inclusivity in creating a productive educational atmosphere